2014
DOI: 10.1542/peds.2014-1295
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Parasomnias: A Longitudinal Cohort Study

Abstract: BACKGROUND AND OBJECTIVES: Environmental factors such as serious trauma or abuse and related stress can lead to nightmares or night terrors. Being bullied can be very distressing for children, and victims display long-term social, psychological, and health consequences. Unknown is whether being bullied by peers may increase the risk for experiencing parasomnias such as nightmares, night terrors, or sleepwalking. METHODS: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 69 publications
3
26
0
9
Order By: Relevance
“…In general, there is evidence that being victimized is associated with sleeping problems (Hunter et al 2014;Tu et al 2017;Wolke and Lereya 2014). According to a recent meta-analysis by van Geel et al (2016), including 21 studies, victimized youth (7-to 19-year-olds) were more than twice as likely to report sleep difficulties (e.g.…”
mentioning
confidence: 99%
“…In general, there is evidence that being victimized is associated with sleeping problems (Hunter et al 2014;Tu et al 2017;Wolke and Lereya 2014). According to a recent meta-analysis by van Geel et al (2016), including 21 studies, victimized youth (7-to 19-year-olds) were more than twice as likely to report sleep difficulties (e.g.…”
mentioning
confidence: 99%
“…Most of the above findings hold up in longitudinal research. Studies have found that, when controlling for sleep disruption in childhood, greater victimization leads to poorer sleep quality and more parasomnias over time (Tu, Spencer, El‐Sheikh, & Erath, ; Wolke & Lereya, ). Additionally, in a longitudinal study predicting both excesses and deficits in sleep (Herge et al, ), cyber victimization was found to directly predict sleep deficit, but relational victimization had a positive indirect effect on both sleep excess and deficit as mediated by depression.…”
Section: Peer Victimization and Physical Health Outcomesmentioning
confidence: 99%
“…More specifically, in one meta-analysis (van Geel et al, 2016), it was concluded that children and young adolescents who were more bullied had more general sleep/wake problems (such as falling asleep or staying asleep; see also Tu, Erath, & El-Sheikh, 2015). Peer victimization has also been related to more experiences of parasomnias (e.g., nightmares, night terrors, and sleep walking; Wolke & Lereya, 2014) and bedtime phobias (Donoghue & Meltzer, 2018). In fact, in an international, cross-cultural study of low-and middle-income countries, victims of bullying were found to have significantly higher ratings of insomnia in comparison to non-victims in all of the 17 countries studied (Fleming & Jacobsen, 2010).…”
Section: Sleepmentioning
confidence: 99%
“…Se ha determinado que las víctimas de acoso escolar son más propensas a exhibir síntomas de problemas somáticos o de salud como dolores de cabeza, dolor abdominal, problemas para dormir, pérdida del apetito y enuresis (Gini y Pozzoli, 2009. Por ejemplo, existe evidencia que asocia el bullying con los problemas para dormir, demostrando que tanto quienes sufren de bullying como quienes lo realizan, tienen patrones de sueño diferentes de aquellos quienes no sufren o realizan bullying (Hunter, Durkin, Boyle, Booth, y Rasmussen, 2014;Kubiszewski, Fontaine, Potard, y Gimenes, 2014), tienen una peor calidad del sueño (Zhou et al, 2015), y las víctimas muestran un mayor riesgo a presentar pesadillas y terrores nocturnos (Wolke y Lereya, 2014).…”
Section: Consecuencias Del Acoso Escolarunclassified